Grey relation projection model for evaluating permafrost environment in the muli coal mining area, China - Cao, Wei; Sheng, Yu; Qin, Yinghong; Li, Jing; Wu, Jichun (International Journal of Mining, Reclamation and Environment, 2010)
This study attempts to estimate the current stage of the permafrost environment in the Muli coal mining area, an opencast mining site in the Qinghai-Tibet plateau, China. The estimation is done by regarding this site's permafrost environment as a system which was divided into three subsystems consisting of permafrost freeze-thaw erosion sensibility, permafrost thermal stability, and permafrost ecological fragility. The subsystems were characterised with their influencing indicators, each of which was assigned with a weight according to analytic hierarchy process. The relationship between these indictors is established using an environmental evaluation model based on grey system theory. The evaluated results show that currently the normalised grey relation projection values (GRPV) of permafrost freezing-thawing erosion sensibility, permafrost thermal stability, permafrost ecological fragility and permafrost environment are 0.58 (general situation), 0.47 (bad situation), 0.63 (general situation) and 0.56 (general situation), respectively. These values imply that the permafrost environment has been deteriorated to a certain degree by human activities and potentially could be further degraded. However, at this degree, a new equilibrium could be achieved if the current environmental degradation ratio is held and if effective treatments are constructed against further damages. © 2010 Taylor & Francis.